Female Subjectivity in Flightplan by Robert Schwentke - Nurwahida, Anisa; Prabasmoro, Tisna; Budhyono, Rasus (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
The historical underrepresentation and misrepresentation of women in the media have the potential to perpetuate gender inequalities and prejudices. This study aims to demonstrate how the film Flightplan by Robert Schwentke depicts female subjectivity and how masculine dominance is shown to affect the female main character's subjectivity, named Kyle Pratt. The researchers use the five C's of cinematographic theory to explore the portrayal of female subjectivity and feminism theory to analyze how the masculine manipulates the main character until her subjectivity arises. The study's findings indicate that although the movie places the female character in a field and situation traditionally dominated by men, it empowers her by portraying her as a character who, with her layered identity as a newly widowed woman, a single mother with one daughter, and a woman herself, who shows her capacity as an independent subject capable of performing qualities and traits normatively constructed as male.